Produksi Kebun Kelapa Sawit Rakyat di Kecamatan Kumai Provinsi Kalimantan Tengah: Penelitian - Holpu Ronal Ambarita; Riantan Chen Yohana Manik (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The agricultural sector plays a significant role in Indonesia's economic activities, with the plantation subsector possessing significant potential. Palm oil is a leading plantation commodity in the Republic of Indonesia. The tropical climate facilitates domestic growth of palm oil plantations. Crude Palm Oil (CPO) is the export product processed by palm oil plantations. Central Kalimantan Province has the largest palm oil plantations, covering approximately 1.6 million hectares. The majority of palm oil plantations in Central Kalimantan are controlled by private companies, covering an area of ​​1.3 million hectares, while smallholder plantations cover 166,000 hectares. Many obstacles are faced by smallholder plantations in maximizing palm oil production in Kumai District, Central Kalimantan. The researchers sought to understand the factors that influence the production of smallholder palm oil plantations. The number of respondents in this study was 100 smallholders, selected using non-probability sampling. This study was conducted over a five-month period, from December 2020 to April 2021. Multiple linear regression analysis was used. The results of the analysis show that land area, number of workers, fertilizer application, and dummy seeds have a significant influence on influencing oil palm plantation production.